Construction and analysis of a green clustered architecture for RNGbased wireless ad hoc networks. (2015) - Tseng, ChihCheng; Ting, KuoChang; Wang, HwangCheng; Kuo, FangChang; Chang, LiHsun
The limited battery power available in the nodes of an ad hoc network makes it mandatory to reduce the energy expenditure. Thus, reducing the transmission distances between nodes and balancing the number of nodes among clusters are two effective approaches to battery power conservation in the design of green wireless ad hoc networks. To realise this goal, the concept of relative neighbourhood graph (RNG) is used to convert the original physical network to an RNGbased logical network. Then, a green clustering algorithm (GCA) is proposed to reorganise the RNGbased logical network into a clustered architecture in which the number of cluster members among clusters is balanced. Finally, a firstorder energy consumption model is applied to analyse the energy consumption in exchanging control messages and transmitting/receiving data packets. Through extensive simulations, it is confirmed that the proposed approaches effectively reduce energy consumption and, thus, extend the battery lifetime.